Acrylic acid conformers and their interactions with dibutyl ether. Issue 6 (3rd July 2022) - Naganandhini, S. P.; Sahana, R.; Mounica, P.; Dineshkumar, P.; Sangeetha, T.; Arivazhagan, G.
Abstract: Fourier Transform Infrared spectra of pure acrylic acid (ARA), dibutyl ether, and their binary solutions at various acid concentrations have been recorded. Density functional theory calculations on ARA monomers and dimers have been carried out. In addition to the cis – cis and trans – trans dimers, cis – trans dimers also exist in liquid acid. The dimer ring formed by carboxyl group has an asymmetry. The experimental asymmetric and symmetric hydroxyl and carbonyl stretching bands have been assigned. Shifts suffered by the absorption bands in binary solutions have been analyzed in view of the formation of heteromolecular hydrogen bonds.